Poorer mental well-being and prior unmet need for mental healthcare: a longitudinal population-based study on men in Sweden - Sara Olsson; Bo Burström; Gunnel Hensing; Jesper Löve (BMC, 2021)
Abstract Background Depression and anxiety disorder contribute to a significant part of the disease burden among men, yet many men refrain from seeking care or receive insufficient care when they do seek it. This is plausibly associated with poorer mental well-being, but there is a lack of population-based research. This study investigated 1) if men who had refrained from seeking mental healthcare at any time in life had poorer mental well-being than those who sought care, 2) if those who had sought care but perceived it as insufficient had poorer mental well-being than those who had perceived care as sufficient, and 3) if these differences persisted after 1 year. Methods This longitudinal study used questionnaire data from a population-based sample of 1240 men, aged 19-64 years, in Sweden. Having refrained from seeking mental healthcare, or perceiving the care as insufficient, at any time in life, was assessed in a questionnaire, 2008. Current mental well-being was assessed in 2008 and 2009 using mean scores on the WHO (Ten) Well-being Index. Lower scores indicate poorer mental well-being. Group differences were calculated using t-tests and multivariable linear regression analysis. Results Of the men who had perceived a need for mental healthcare, 37% had refrained from seeking such care. They had lower mental well-being scores in 2008, compared to those who sought care. Of those seeking care, 29% had perceived it as insufficient. They had lower mental well-being scores in 2008, compared to those who perceived the care as sufficient, but this was not statistically significant when controlling for potential confounders. There were no differences in mental well-being scores based on care-seeking or perceived care-sufficiency in 2009. Conclusions This population-based study indicates that men who have previously refrained from seeking mental healthcare, or perceived the care as insufficient, have poorer mental well-being. However, the lack of differences at the one-year follow-up contradicts these results. The results highlight the need for larger longitudinal studies, measuring care-seeking within a more specified time frame. This should be combined with efforts to increase men's mental healthcare-seeking and to provide mental healthcare that is perceived as sufficient.